2005
DOI: 10.4103/0970-4388.16030
|View full text |Cite
|
Sign up to set email alerts
|

Dentigerous cyst associated with permanent central incisor: A rare entity

Abstract: Dentigerous cyst is one of the most prevalent types of odontogenic cyst and is associated with crown of an unerupted or developing tooth. Dentigerous cyst is more commonly seen with mandibular third molar and maxillary canine and rarely other teeth are involved. Here we report a case of dentigerous cyst involving permanent maxillary central incisor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…In contrast to this, few authors have reported radicular cyst in deciduous anterior teeth following traumatic injury [14,15]. Whereas many authors [16,17,18] have reported dentigerous cyst as a common sequelae following trauma to the primary predecessor, radicular cysts are comparatively rare. The reasons behind this controversy have not been clearly understood.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to this, few authors have reported radicular cyst in deciduous anterior teeth following traumatic injury [14,15]. Whereas many authors [16,17,18] have reported dentigerous cyst as a common sequelae following trauma to the primary predecessor, radicular cysts are comparatively rare. The reasons behind this controversy have not been clearly understood.…”
Section: Discussionmentioning
confidence: 76%
“…A distinção radiográfica se torna de alguma forma arbitrária; no entanto, qualquer área radiolúcida pericoronária que seja maior de 4 ou 5 mm é considerada sugestiva de formação cística e deveria ser submetida a exame microscópico de rotina 2 . Uma extensa lesão pode dar a impressão de um processo multilocular por causa da persistência de osso trabecular dentro da área radiolúcida.…”
Section: Resultsunclassified
“…São lesões relativamente incomuns da região oral e maxilofacial, devendo ser consideradas sempre que forem formulados diagnósticos diferenciais de um processo de expansão dos maxilares 1 . Com raras exceções, cistos revestidos por epitélio no osso são vistos somente nos maxilares 2 . Pouco mais do que alguns cistos podem resultar da inclusão do epitélio ao longo das linhas embrionárias de fusão, sendo que a maioria dos cistos dos maxilares são revestidos pelos componentes do epitélio odontogênico 3 .…”
unclassified
“…Total enucleation for small lesions [1,18] and marsupialization for decompression of large volume cysts; or 2. a combination of both [19][20][21].…”
Section: Discussionmentioning
confidence: 99%